Synthesis of polydicyclopentadiene using the Cp2TiCl2/Et2AlCl catalytic system and thin-layer oxidation of the polymer in air - Bazarova, Zhargolma B.; Soroka, Ludmila S.; Lyapkov, Alex A.; Yusubov, Мekhman S.; Verpoort, Francis (Beilstein Journal of Organic Chemistry, 2019)
The polymerization process of dicyclopentadiene using a multicomponent catalytic system based on bis(cyclopentadienyl)titanium dichloride and diethylaluminum chloride was studied. It was demonstrated that the application of an excess of the aluminum component leads to the formation of stable charged complexes of blue discoloration, which initiate cationic polymerization of dicyclopentadiene. Unstabilized thin layers of obtained polydicyclopentadiene undergo oxidation and structuring under atmospheric oxygen. Oxidation of polydicyclopentadiene films in air occurs slowly during several weeks and can be determined by the increase of carbonyl and hydroxyl adsorption bands in infrared spectra. Along with oxidation, cross-linking processes occur in polymers, which lead to a change in physical parameters of the layers, and more precisely to a decrease in the permeability of atmospheric oxygen through the layers. Consequently, this leads to the transition of the oxidation from a kinetic mode into a diffusive mode. Such structural changes do not occur in a polymer that was stabilized by adding an antioxidant.
Keywords: bis(cyclopentadienyl)titanium dichloride; cationic polymerization; oxidation; polydicyclopentadiene; thin layers